Bankruptcy Prediction Analysis Using The Springate S-Score Method in Automotive and Component Subsector Companies in 2019-2023 - Ayu Anggraeni; Maria Theresia Heni Widyarti; Siti Arbainah (Applied Accounting and Management Review (AAMAR), 2025)
This study aims to analyze the financial condition of Automotive and Component Subsector Companies listed on the Indonesia Stock Exchange in 2019-2023. The sample companies used were 10 out of 18 companies taken using purposive sampling techniques. The research method used is quantitative descriptive, which examines secondary data in balance sheets and company income statements. The analysis was carried out using the Springate S-Score Method, which consists of 4 ratios: Working Capital to Total Assets, Earning Before Interest and Tax to Total Assets, Earning Before Tax to Current Liabilities, and Sales to Total Assets. The study results show that, on average, automotive and component subsector companies are in good health or have not gone bankrupt. So, the company needs to maintain its financial condition to avoid bankruptcy.